Entre o porão e o lustre: a relação personagem e espaço no romance O lustre, de Clarice Lispector - Santos, Joelice Barbosa dos (2008)
The central object of this research is the analysis of the novel O Lustre, by Clarice Lispector. Some theoretical reflections about the modern novel, as well as the criticism about this book, helped us in this study. Therefore, the present work does not base itself only in the theoretical discussion, but in the critical voice too, which did not recognize this literary work of 1946 as criticism did with the others novels by this author. The observations about the Aesthetics of Reception, proposed by Hans Robert Jauss, served to draw up the way in which the horizon of expectations about this novel developed. From this approach, we can observed that the question about the convention of the genres in the Lispector s work was a key factor that bothered many critics. Actually, this book does not follow the straight rules of the traditional novel. In this novel, the character stands out in the process of construction and the relations with the space. For this, it is transforming according to the place where it is. Gaston Bachelard s concepts were the base to analyze the space in this novel. The central attention about the question of space was based in the discussions that appear in his book The Poetics of the Space. The importance of the O Lustre in Lispector s work is also noted in the quotations from the other authors which appear in this narrative, as Edgar Allan Poe. Moreover, this book presents various relations with other arts. The present research wishes to contribute with the studies about Lispector s work. Especially with a novel considered minor in the Brazilian writer s production